Bidirectional Tracking Robust Controls for a DC/DC Buck Converter-DC Motor System - Eduardo Hernández-Márquez; José Rafael García-Sánchez; Ramón Silva-Ortigoza; Mayra Antonio-Cruz; Victor Manuel Hernández-Guzmán; Hind Taud; Mariana Marcelino-Aranda (Complexity)
Two differential flatness-based bidirectional tracking robust controls for a DC/DC Buck converter-DC motor system are designed. To achieve such a bidirectional tracking, an inverter is used in the system. First control considers the complete dynamics of the system, that is, it considers the DC/DC Buck converter-inverter-DC motor connection as a whole. Whereas the second separates the dynamics of the Buck converter from the one of the inverter-DC motor, so that a hierarchical controller is generated. The experimental implementation of both controls is performed via MATLAB-Simulink and a DS1104 board in a built prototype of the DC/DC Buck converter-inverter-DC motor connection. Controls show a good performance even when system parameters are subjected to abrupt uncertainties. Thus, robustness of such controls is verified.